Exploring the influence of financial technology on banking services in Nigeria - Otonne, Adewumi; Ige, Olaoluwa Tosin (Goodwood Publishing, 2023)
Purpose: This study explored the impact of fintech on Nigerian banking services. Research methodology: This study employed a quantitative research approach, analyzing data from the financial statements of selected Nigerian banks, and financial technology application statistics through econometric modelling and descriptive analysis. Results: The study found that Fintech positively impacts Nigerian banks' traditional and market-based performance measures. For example, statistically, a 1 per cent increase in ATM transactions could increase banks' earnings per share by up to N4 on average. This implies that fintech adoption in the Nigerian financial system can increase efficiency, reduce costs, improve the customer experience, and enhance financial inclusion. Limitations: This study had several limitations, such as the unavailability of data for some banks and the limited timeframe due to data unavailability. Contribution: This study contributes to the growing body of literature on fintech in emerging markets by providing insights into Nigeria’s evolving fintech landscape and its potential impact on traditional banking services. Novelty: This study is one of the first to investigate the impact of fintech on Nigerian banking services based on selected case studies and the quantitative research approach employed. This study provides valuable insights for policymakers, regulators, and industry practitioners seeking to promote a conducive environment for fintech growth in Nigeria’s banking sector.